Art as a "middle point" and its classicism - Vieweg, Klaus (Estudios de Filosofía, 2005)
Due to Hegel’s interest in the historical function of art as a cultural component, his philosophy of art is inseparable from his philosophy of history. The universal forms of art (symbolic, classic and romantic) correspond both to the formative process of and to the realization of human subjectivity and its liberty in the eastern world, in the classical or greek world and in the modem world. The article focuses on the classical form, that is the world of greek culture its classicism is a "middle point" because it is situated in the realm of beauty, between nature and liberty. Even though it is beautiful, the art of the classic form is to us. moderns, an art of the past, it is an art for the liberty of a citizen of the polis, but not for the universal and individualized freedom of a cosmopolitan citizen.